Synthesis and thermal studies of solid state 2-chloro-benzylidenepyruvic acid and its compounds with sodium, aluminium (III), gallium (III) and indium (III) cations - Bannach, Gilbert [UNESP]; Schnitzler, E.; Melios, C. B. [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2004)
A síntese do 2-clorobenzalpiruvato de sódio e seu respectivo ácido, bem como compostos binários, compostos binários junto com seu respectivo ácido ou hidroxo-2-clorobenzalpiruvato de alumínio (III), gálio (III) e de índio (III), foram isolados. Na caracterização e estudo do comportamento térmico desses compostos foram utilizados a termogravimetria, termogravimetria derivada (TG/DTG), termogravimetria-analise térmica diferencial simultânea (TG-DTA), difratometria de raios X pelo método do pó e análise química. Os resultados forneceram informações com respeito a estequiometria, cristalinidade, estabilidade e decomposição térmica.

The synthesis of sodium 2-chlorobenzylidenepyruvate and its corresponding acid as well as binary, binary together with it's acid or hydroxo-2-chorobenzylidenepyruvate of aluminium (III), gallium (III) and indium (III), were isolated. Chemical analysis, thermogravimetry, derivative thermogravimetry (TG/DTG), simultaneous thermogravimetry-differential thermal analysis (TG-DTA) and X-ray powder diffractometry have been employed to characterize and to study the thermal behaviour of these compounds. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition.
Síntese e estudo térmico do ácido 2-clorobenzalpirúvico e dos benzalpiruvatos de sódio, alumínio (III), gálio (III) e índio (III) no estado sólido
Keywords: ácido 2-clorobenzalpirúvico; 2-clorobenzalpiruvato; sódio; alumínio; gálio; índio; comportamento térmico; 2-chlorobenzylidenepyruvic acid; 2-chlorobenzylidenepyruvate; sodium; aluminium; gallium; indium; thermal behaviour